2019
DOI: 10.3390/su11051269
|View full text |Cite
|
Sign up to set email alerts
|

Methane Production from Alginate-Extracted and Non-Extracted Waste of Laminaria japonica: Anaerobic Mono- and Synergetic Co-Digestion Effects on Yield

Abstract: This study investigated the potentiality of methane production from alginate-extracted (AEWLJ) and non-extracted (NAEWLJ) waste of Laminaria japonica through batch anaerobic fermentation in mono- and co-digestion with rice straw (RS) at different mixing ratios. Optimal C/N ratio was demonstrated, and system stability was monitored in terms of the total ammonia nitrogen, total volatile fatty acids, and pH throughout the digestion period. The results show that the combination of AEWLJ/RS at 67% mixing ratio gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…The results showed that co-digestion of AEWLJ/RS at 67% mixing ratio produced the highest biogas yield of 247 mL/g VS, being 36% higher than the AEWLJ alone. The synergetic effect improved the total methane yield up to 78% and 88% for combinations of AEWLJ/RS and NAEWLJ/RS, respectively [93].…”
Section: Microbial Community Structure and Synergymentioning
confidence: 96%
“…The results showed that co-digestion of AEWLJ/RS at 67% mixing ratio produced the highest biogas yield of 247 mL/g VS, being 36% higher than the AEWLJ alone. The synergetic effect improved the total methane yield up to 78% and 88% for combinations of AEWLJ/RS and NAEWLJ/RS, respectively [93].…”
Section: Microbial Community Structure and Synergymentioning
confidence: 96%
“…[32,[43][44][45][46] Government laws and subsidies Creation of regulation and incentive laws for the use of biodigesters [33,47] Waste reuse Reuse of residues by means of the anaerobic digestion that takes place inside the biodigester [31,43,[48][49][50] Availability of large quantities of raw materials Large amounts of animal and vegetable waste generation can be used to supply the biodigesters. [31,38,[50][51][52] Nearby production and consumption…”
Section: Facilitators Description Referencesmentioning
confidence: 99%
“…Both were higher than respective control digesters (control digester A = 1.91% and control digester A = 20.61%). Osman et al [52] in their study for evaluation of methane yield from different ratios of alginate-extracted (AEWLJ) and non-extracted (NAEWLJ) waste of Laminaria japonica in mono and co-digestion with rice straw (RS) used the modified Gompertz equation. Syaichurrozi [51] reported the highest biogas yield of 113.92 ± 6.90 mL/g VS in co-digestion of aquatic weed Salvinia molesta (SM) and rice straw (RS) at the mass ratio of 40:60.…”
Section: Kinetics Of Biogas Productionmentioning
confidence: 99%